Functional annotation of variants from healthy individuals - Jean Lee; Sung Eun Hong (Genomics & Informatics)
The implications of germline de novo variants (DNVs) in diseases are well documented. Despite extensive research, inconsistencies between studies remain a challenge, and the distribution and genetic characteristics of DNVs need to be precisely evaluated. To address this issue at the whole-genome scale, a large number of DNVs identified from the whole-genome sequencing of 1,902 healthy trios (i.e., parents and progeny) from the Simons Foundation for Autism Research Initiative study and 20 healthy Korean trios were analyzed. These apparently nonpathogenic DNVs were enriched in functional elements of the genome but relatively depleted in regions of common copy number variants, implying their potential function as triggers of evolution even in healthy groups. No strong mutational hotspots were identified. The pathogenicity of the DNVs was not strongly elevated, reflecting the health status of the cohort. The mutational signatures were consistent with previous studies. This study will serve as a reference for future DNV studies.